Pengaruh Work Life Balance dan Kecerdasan Emosional terhadap Organizational Citizenship Behavior (OCB) - Simanjorang, Helentina; Elvinawanty, Rianda; Sinaga, Refina Lestari; Laia, Bernadet Selfiana; Hartini, Sri (Universitas Darul Ulum, 2025)
This study examines how Work-Life Balance and Emotional Intelligence affect organizational citizenship Behavior. The study sampled 110 YPK Don Bosco Saribudolok elementary-junior high school teachers. The major hypothesis proposed in this study is that there is an influence of Work-Life Balance and Emotional Intelligence on OCB in YPK Don Bosco Saribudolok teachers. The first minor hypothesis is that there is a positive relationship between Work-Life Balance and OCB, and the second hypothesis is that there is a positive relationship between Emotional Intelligence and OCB. This study included multiple regression analysis and assumption tests such as normality, multicollinearity, autocorrelation, and heteroscedasticity. Regression analysis (F = 3.563, p = 0.032, p < 0.05) supports the major hypothesis that Work-Life Balance and Emotional Intelligence impact OCB. The research findings for each minor hypothesis test showed no relationship between Work-Life Balance and OCB (β = 0.97, p = 0.300). This finding indicates that the first minor hypothesis is rejected. Meanwhile, a relationship was found between Emotional Intelligence and OCB (β = 0.228, p = 0.017), which reflects the acceptance of the second minor hypothesis. According to the research, work-life balance and emotional intelligence contribute 4.5 percent to corporate citizenship behavior. The remaining 95.5 percent is affected by unstudied causes.